Characteristics of an efficient tax system: The case of Malaysian indirect tax - Mansor, Muzainah; Tayib, Mahamad; Yusof, Rohana @ Norliza (Universiti Utara Malaysia, 2004)
The issue of achieving the right ingredient to have a better tax system is not new, as many believed that Adam Smith’s cannons of taxation are still the focus point in setting up any taxation systems. It is undeniable that Adam Smith’s formula is still relevant, however today’s globalization and trade liberalization may reduce the economic distances between nations and therefore will create several challenges to tax structures around the world. As a matter of fact, the challenges may influence the level of tax revenue, tax mix and systems of tax administration and compliance. Each country has to have a competitive and efficient tax system in facing globalization and trade liberalization. With regards to this, tax academics and practitioners around the world have put forward the suggestions to the governments for better tax systems. The ICAEW for example, has recommended ten tenets towards a better tax system in the UK. Meanwhile, CPA Australia has proposed a framework paper on road rules and a road map for a better tax policy in Australia. In developing countries with emerging markets such as Malaysia, which aims to integrate with international economy, the tax system plays a particularly important role. The tax system should be able to raise revenue to finance essential expenditures while minimizing disincentive effects on economic activities, without deviating from international norms. Previous studies suggested that a good tax system as perceived by the taxpayers would result in high compliance towards the payment of the taxes imposed on them. Generally, based on the respondents surveyed, there are mixed responses for each characteristics as perceived by the taxpayers. The findings revealed that there is an existence of a good legislation under the tax system; and the tax system is constant and regularly reviewed. However, they disagree that the present system is certain and simple; proper consultation has been made before any new legislation is issued; and that the overall system is fair. From all the characteristics suggested, the taxpayers ranked ‘statutory’ as the highest and ‘proper consultation’ as the lowest.